Risk factors for actinic cheilitis: A meta-analysis - Alberto Rodriguez-Archilla; Amna Irfan-Bhatti (Tabriz University of Medical Sciences, 2021)
Background. Actinic cheilitis (AC) is a potentially malignant disorder characterized by chronic lip inflammation, especially the lower lip, associated with accumulative exposure to solar radiation. The present study aimed to assess the possible risk factors related to AC. Methods. A search for studies on AC risk factors was conducted in the following databases: PubMed (MEDLINE, Cochrane Library), Web of Science (WoS), and Google Scholar. For dichotomous outcomes, the estimates of the effects of intervention were expressed as odds ratios (ORs) using Mantel-Haenszel (M-H) method, and for continuous outcomes, the estimates of the effects of intervention were expressed as mean difference (MD) using the inverse variance (IV) method, both with 95% confidence intervals. Results. Twelve studies were considered in this meta-analysis. The factors from the highest to lowest risk of AC were having a low skin phototype (OR: 3.30), age >50 years (OR: 3.01), having high sun exposure, cumulative throughout life (OR: 2.13) as daily (OR: 2.00), being male (OR: 1.78), and being a drinker (OR: 1.56) or smoker (OR: 1.32). However, the use of sunscreen creams and caps/hats to protect against the sun were factors with no significant influence on the AC risk. Conclusion. Chronic sun exposure in subjects with low skin phototypes is the main risk factor for AC.